Analisis kinerja turbin air arus bawah bentuk sudu bengkok dengan variasi material - Duma, G. A.; Sule, L. (Universitas Mataram, 2022)
A water turbine is a device used to convert the potential energy of water into mechanical energy. This mechanical energy is then converted into electrical energy by a generator. This test was carried out experimentally using a crooked blade type with six blades and the type of water turbine used was undershoot. Various types of blade materials are plastic, aluminium, and iron. As well as varying the opening of fluid flow, namely the valve opening of 25%, 50%, 75%, and 100%. The results obtained indicate that variations in turbine blade material have an effect on turbine power and turbine efficiency The highest turbine power and efficiency was obtained at 100% valve opening with a load of 0.7 kg on plastic, iron and aluminium material. The highest turbine power is 1.16 watts for the plastic blade, the aluminium blade is 1.22 watts, and for the iron, the blade is 1.1 watts. The highest efficiency obtained for plastic blades is 50.14 % for experiment and theoretical is 5.67%, aluminium blades are 52.77% for experiment and 54.41% for theoretical, iron blades are 47.5% for experiment and 48.97% for theoretical.